Review on water footprint method in different sectors - Kalvani, Somayeh Rezaei; Sharaai, Amir Hamzah; Abd Manaf, Latifah; Hamidian, Amir Hossein (Science and Engineering Research Support Society, 2020)
The water footprint (WF) method is a comprehensive approach for evaluating direct and indirect water consumption in different sectors, including the industrial, agricultural, and domestic sectors. Recently, different approaches for the assessment of water consumption in production processes have been introduced. In the WF method, water consumption (with regard to quality and quantity) at high spatial and temporal resolution can be included as well. Water footprint is a simple and valuable approach for the evaluation of water use. In spite of the widespread enthusiasm for using the water footprint method, some weaknesses have been raised regarding this approach. Water footprint assessment in domestic sector consumption, e.g. showering, is not included. Besides that, the WF method does not evaluate blue water separately as ground and surface WF. Furthermore, most water footprint research have been conducted in agricultural sectors in different provinces of China. Additionally, water footprint assessment in the industrial sector is complex and requires a lot of data. There is inadequate framework for the evaluation of water consumption in the municipal scale, should the water footprint method be used. There is a lack of study in the evaluation of water footprint on a municipal level. The grey WF is important for evaluating water consumption in the industrial sector.